Effectiveness of an autovaccine in a case of canine papillomavirus in a Great Dane dog in Costa Rica - Alfaro-Mora, Ramsés (2022)
The aim of this study was to determine the effectiveness of an autovaccine for papilloma caused by canine papillomavirus (CPV) in the facial region in a three-month-old Great Dane dog. A group of papillomas were collected from the patient’s face and analyzed using molecular techniques (amplification of a segment of the gene that codes for the L1 protein by PCR and sequencing). For sequence analysis, the BLAST algorithm was used. The histological study was performed by hematoxylin-eosin staining of the tissue and analysis under a 20X light microscope. An autovaccine was developed from the excised papillomas, which was administered intradermally on four occasions at seven-day intervals. The presence of genotype 1 CPV was established in the papilloma analyzed. Histopathology established the formation of exophytic epidermal papillae supported by a fibrovascular chorion with hyperkeratosis (orthokeratotic) and hyperplasia of the stratum spinosum and with keratinocytes (koilocytes). The papillomas disappeared after the third application of the autovaccine. This is the first CPV-1 report in Costa Rica. The autovaccine proved to be an effective treatment in the management of facial papillomatosis in the patient.